1986
DOI: 10.1128/mcb.6.8.2884
|View full text |Cite
|
Sign up to set email alerts
|

Negative and positive regulation in trans of gene expression from adeno-associated virus vectors in mammalian cells by a viral rep gene product.

Abstract: We previously described use of the human parvovirus, adeno-associated virus (AAV), as a vector for transient expression in mammalian cells of the gene for chloramphenicol acetyltransferase (CAT). In the AAV vector, pTS1, the CAT gene is expressed under the control of the major AAV promoter p4o. This The human parvovirus, adeno-associated virus (AAV), replicates in mammalian cells in the presence of helper functions provided by adenovirus or herpesvirus (10). When molecular clones containing the entire AAV ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 64 publications
5
143
1
Order By: Relevance
“…To test this possibility experiments have been done in which the transient expression of CAT activity has been measured when CAT constructs under control of the SV40 early promoter have been co-transfected with AAV plasmids. Transient expression of CAT activity is also blocked by the presence of a functional AAV rep gene (M. A. Labow, L. H. Graf & K. I. Berns, unpublished observations;Tratschin et al, 1986). Therefore, it seems likely that the major inhibitory effect on permanent transformation seen when AAV plasmids are co-transfected with selectable markers on separate plasmids is also at the level of inhibition of gene expression.…”
Section: Additional Inhibitory Effects Of the Aa V Rep Gene Productsmentioning
confidence: 98%
See 3 more Smart Citations
“…To test this possibility experiments have been done in which the transient expression of CAT activity has been measured when CAT constructs under control of the SV40 early promoter have been co-transfected with AAV plasmids. Transient expression of CAT activity is also blocked by the presence of a functional AAV rep gene (M. A. Labow, L. H. Graf & K. I. Berns, unpublished observations;Tratschin et al, 1986). Therefore, it seems likely that the major inhibitory effect on permanent transformation seen when AAV plasmids are co-transfected with selectable markers on separate plasmids is also at the level of inhibition of gene expression.…”
Section: Additional Inhibitory Effects Of the Aa V Rep Gene Productsmentioning
confidence: 98%
“…It was noted earlier that Tratschin et al (1986) had found that the regulatory effects of the AAV rep gene products were different when only the Ad E 1A and E 1B products were present in the cell compared to when there was a productive Ad infection. Among the additional Ad genes required for AAV replication is E4.…”
Section: Additional Inhibitory Effects Of the Aa V Rep Gene Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The terminal repeats which form well defined secondary structures serve as origins of DNA replication; the cap gene encodes the three viral capsid proteins; the rep gene encodes four non-structural proteins with Mrs of 78000, 68000, 52000 and 40000 (Mendelson et al, 1986). These proteins are involved in AAV-2 DNA replication and in the regulation of AAV-2 gene expression (Tratschin et al, 1986;Beaton et al, 1989).…”
mentioning
confidence: 99%